Tobacco use and parental monitoring - observations from three diverse island nations: Cook Islands, Curaçao, and East Timor - Shaikh, Masood; Zare, Zahra; Ng, Kwok W.; Celedonia, Karen; Wilson, Michael (International journal of environmental research and public health, 2020)
Tobacco use among adolescents is a global problem of public health importance. This study examined the profile of differences and similarities in adolescent tobacco use, and the role of parental monitoring activities among adolescents in three island nations of varying economic status: Cook Islands, Curaçao, and East Timor. Using nationally representative data we conducted regression modeling to determine the effect of four types of parental monitoring activities on tobacco use. Within a recall period of 30 days prior to being surveyed, 29.7% of students in East Timor, 21.6% in Cook Islands, and 13.1% in Curaçao reported having smoked cigarettes and/or used tobacco in other forms during 1 or more days during the preceding 30 days. Lower rates of parental monitoring as measured by four variables (parental understanding of problems and worries; knowing about how free time was being spent; going over things without approval; and checking to see if homework was done) were associated with higher percentages of adolescent tobacco use. Taken together the results underscore the need for increased parental involvement in programs which are designed to reduce tobacco use among adolescents.
Gesehen am 26.10.2020